Kegiatan Bermain Seni Rupa Berbasis Konsep Tri Pramana Di Tk Bali Kumara Desa Batubulan - Suryawan, I Gde; Dewi, Putu Ayu Septiari; Anadhi, I Made Gede; Suardika, Komang; Jayadiningrat, Made Gautama (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This service aims to educate and provide understanding through visual arts play activities based on the Tri Pramana concept at the Bali Kumara Kindergarten, Batubulan Village. The Tri Pramana concept, which consists of Pratyaksha Pramana (direct observation), Anumana Pramana (thinking or reasoning), and Agama Pramana (experience received from inherited teachings), is used as a framework for designing and presenting visual arts activities that are attractive to children -early childhood. The method of carrying out community service activities is lectures and demonstrations. The lecture method is a form of presenting teaching material through information and oral narrative by the service team to students. The activities that will be carried out include the delivery of material regarding the concept of fine arts play activities in the form of a prayer posture, implementation of activities in the form of demonstrations by the service team and direct practice of fine arts made from natural materials. Data was collected through participant observation, interviews with teachers, and analysis of documentation of works of art produced by children. The results of the service show that visual arts play activities based on the Tri Pramana concept provide a rich and meaningful learning experience for children. They not only learn to observe and express themselves through art, but also develop critical thinking skills and an appreciation of art and culture. Implementation of the Tri Pramana concept in fine arts play activities at Bali Kumara Kindergarten in Batubulan Village can be an effective model for increasing understanding of fine arts and developing critical thinking in early childhood. This service makes a valuable contribution to the development of fine arts education at the pre-school level and enriches the practice of fine arts education in general.